Effect of the application of work study on the productivity of a manufacturing company-Peru (LACCEI, 2024)
The main objective of the research was to determine the effect of the application of work study on the productivity of a manufacturing company. For some years now, worldwide, companies in this field have been seeking to improve their productivity, in order to compete in the market and satisfy customer requirements. This study was of an applied type, since it sought to verify the theoretical part with reality the design was pre-experimental with a quantitative approach, in addition the population and sample were the activities of the productive process of the brick. A check list, observation guide and data sheet were used as instruments. It was obtained as a result that the multifactorial productivity increased to 1,878 bricks for each sun invested, the labor productivity to 32,225 bricks for each man hour and the raw material to 0.105 kg bricks for each kg of raw material used. For all these reasons, it is concluded that the application of the study of work has a positive effect on the productivity of a manufacturing company, being evidenced by the increase in productivity, which went from 1,322 to 1,878, representing a variation of 42.1%.